The Effect of Product Quality, Brand Image, Electronic Word of Mouth and Packaging on Purchasing Decisions - Aqsha Anantha; Arini Hidayah; Totok Haryanto; Restu Frida Utami (Trescode Green Organization, 2024)
This study aims to assess the impact of Product Quality, Brand Image, Electronic Word of Mouth (EWOM), and Packaging on the purchasing decisions for Hot Wheels diecast cars. The study's population includes individuals who have bought Hot Wheels products and are members of the Hot Wheels Indonesia community, with a sample size of 115 respondents as determined by the researcher. The purposive sampling method was used, and data analysis was conducted with multiple linear regression and correlation using SPSS version 26. The findings indicate that the product quality variable (KUAL) significantly influences purchasing decisions (KP) for Hot Wheels diecast cars, while the brand image variable (BI) does not have a significant impact on purchasing decisions. Both the electronic word of mouth (EWOM) and packaging (KEM) variables significantly affect purchasing decisions. In summary, product quality, brand image, electronic word of mouth, and packaging all have a positive and significant impact on purchasing decisions.